2019
DOI: 10.1007/s11096-019-00869-5
|View full text |Cite
|
Sign up to set email alerts
|

Moral reasoning among Dutch community pharmacists: testing the applicability of the Australian Professional Ethics in Pharmacy test

Abstract: Background Moral reasoning competency is essential in healthcare practice, especially in situations of moral dilemmas when a professional has to choose a morally justifiable action among several suboptimal action options. The Australian Professional Ethics in Pharmacy test (PEP test) measures moral reasoning among pharmacists. In Australia three levels of moral reasoning (schemas) were measured (1) business orientation (2) rules and regulations, and (3) patient rights (i.e. most advanced schema). Objective To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The respondents answered 12 items corresponding to three themes: business orientation, rules and regulations, and patients' rights. Kruijtbosch et al (2019) conducted the PEP test in the Netherlands and reported a difference in the schematic structure from Australia. The Engineering and Science Issues Test (ESIT) was also derived from DIT-2, and includes six dilemma scenarios that a scientist or engineer is likely to encounter (Borenstein et al 2010).…”
Section: Measuring Ethicsmentioning
confidence: 99%
“…The respondents answered 12 items corresponding to three themes: business orientation, rules and regulations, and patients' rights. Kruijtbosch et al (2019) conducted the PEP test in the Netherlands and reported a difference in the schematic structure from Australia. The Engineering and Science Issues Test (ESIT) was also derived from DIT-2, and includes six dilemma scenarios that a scientist or engineer is likely to encounter (Borenstein et al 2010).…”
Section: Measuring Ethicsmentioning
confidence: 99%
“…Pharmacists need to be competent in ethical decisionmaking to enable them to act in a morally preferable and justifiable manner with patients in everyday practice (Kruijtbosch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%